Exploring suture pharyngoplasty outcomes in OSA: A tertiary hospital experience - Padmanabhan, Karthikeyan (IP Indian Journal of Anatomy and Surgery of Head Neck and Brain, 2025)
The study evaluates the efficacy of suture pharyngoplasty in managing obstructive sleep apnea (OSA) through a case series of 25 patients. OSA, characterized by recurrent upper airway collapse during sleep, results in fragmented sleep, intermittent hypoxia, oxygen desaturation, and systemic complications. Despite continuous positive airway pressure (CPAP) being the standard treatment, its poor tolerance necessitates alternative approaches. Suture pharyngoplasty, combined with lifestyle modifications, was assessed as a minimally invasive surgical solution targeting lateral pharyngeal wall collapse. Patients aged 18–60 with mild to moderate OSA underwent preoperative assessments, including polysomnography, Epworth Sleepiness Scale (ESS), and STOP-BANG criteria. Postoperative evaluations at three and six months revealed significant reductions in the Apnea-Hypopnea Index (AHI) and oxygen desaturation episodes. Notable improvements in oxygen saturation, ESS scores, and STOP-BANG scores were observed, reflecting enhanced sleep quality and reduced disease severity. The procedure demonstrated a favorable safety profile, with no major complications and only minor, transient postoperative discomfort. The results affirm the potential of suture pharyngoplasty in effectively reducing OSA severity, improving patient-reported outcomes, and achieving sustained benefits with minimal risk. This series aligns with existing literature, supporting the procedure as a viable alternative for carefully selected patients. The findings underscore the role of suture pharyngoplasty as a promising addition to OSA management strategies, emphasizing the need for further validation in broader patient populations.